Does Flypaper Effect Really Exist? Evidence From Government Budget in East Indonesia - Rizki Ramadhani; Farah Nisa Ul Albab; Aryan Danil Mirza. BR (Universitas Teknologi Yogyakarta, 2022)
Regional autonomy is one form of policy from the Indonesian central government to encourage independence from every existing local government, but at the same time, it also creates economic inequality. To make it balanced, the central government provides transfer funds for every local government that needs it. However, the dependence of the local government on the central government transfer funds has led to the phenomenon called the Flypaper Effect. This study aims to see the effect and the existence of a flypaper towards Local Own-Source Revenue (Pendapatan Asli Daerah), General Allocation Fund (Dana Alokasi Umum), Special Allocation Fund (Dana Alokasi Khusus), Revenue Sharing Fund (Dana Bagi Hasil) and Local Expenditure. This study relays on audited financial statements of local governments in 11 provincial governments located in Eastern Indonesia from 2012-2017. It uses E-views to test the hypothesis. The results show that only the Special Allocation Fund does not affect Local Expenditure. Furthermore, in Eastern Indonesia, there is an existing flypaper effect phenomenon. The regional autonomy policy implementation still needs to be improved. The central government needs to motivate the local government potencies to maximize their original revenue and consider for adjust the policy itself.